Unmasking of latent synaptic connections in the cortex of the rat, elicited by facial nerve transection - Farkas, Tamás; Toldi, József (Acta Biologica Szegediensis, 2001)
Peripheral nerve injury elicits plastic changes in the cortex, resulting in reorganization of the somatotopic representation maps. These processes begin within minutes after nerve injury, and last for weeks. Although the mechanisms leading to these plastic changes are not known in a detail, a number of results suggest that the key element in the starting of these processes is a decrease in the function of the cortical GABAergic system, which allows the unmasking of pre-existing but normally silent synapses. The somatosensory and motor cortices of the rat brain are involved in strong and mutual interaction. This study of the early changes induced in this relationship by unilateral facial nerve transection (N7x) revealed that the disinhibition of associational and commissural connections caused by N7x allowed the appearance and enhancement of potentials in the motor cortices on both sides, evoked by right-side trigeminal stimulation, though these responses were strictly lateralized in normal animals. In response to the juxtacellular application of GABA and muscimol, reversal was observed in a small population of neurons (3 out of 84) tested with microelectrode recordings and pressure microinjections. These results suggest that a peripheral nerve injury (N7x) rapidly induces GABAA receptor-dependent disinhibition in the cortex.